2020
DOI: 10.3390/agriculture10080309
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous Oil Crops, a Review on Mechanical Harvesting State of the Art

Abstract: The sustainable production of renewable energy is a key topic on the European community’s agenda in the next decades. The use of residuals from agriculture could not be enough to meet the growing demand for energy, and the contribution of vegetable oil to biodiesel production may be important. Moreover, vegetable oil can surrogate petroleum products in many cases, as in cosmetics, biopolymers, or lubricants production. However, the cultivation of oil crops for the mere production of industrial oil would arise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 182 publications
(219 reference statements)
1
32
0
Order By: Relevance
“…According to our findings, a similar result can be obtained without using the specific header. In fact, only 3.2% w/w of the seed loss was found and this is consistent with the findings reported in similar studies dealing with the mechanical harvesting of other oil seeds, namely: 0.97-2.76% w/w in canola (Brassica napus L.) [54,55], about 3% w/w in safflower (Carthamus tinctorius L.) [26] and crambe (Crambe cabyssinica Hochst) [56], and 2% w/w in sunflower [57], although reducible to less than 1% w/w if particular adjustments are applied [58,59]. Nevertheless, it is dutiful to underline that the specific cardoon header described by Pari et al was specifically developed to prevent the subsequent use of a shredder to manage the left aboveground biomass [28,30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to our findings, a similar result can be obtained without using the specific header. In fact, only 3.2% w/w of the seed loss was found and this is consistent with the findings reported in similar studies dealing with the mechanical harvesting of other oil seeds, namely: 0.97-2.76% w/w in canola (Brassica napus L.) [54,55], about 3% w/w in safflower (Carthamus tinctorius L.) [26] and crambe (Crambe cabyssinica Hochst) [56], and 2% w/w in sunflower [57], although reducible to less than 1% w/w if particular adjustments are applied [58,59]. Nevertheless, it is dutiful to underline that the specific cardoon header described by Pari et al was specifically developed to prevent the subsequent use of a shredder to manage the left aboveground biomass [28,30].…”
Section: Discussionsupporting
confidence: 91%
“…While, the harvest of the aboveground biomass takes place in the summer, using different machines according to the purpose of cultivation, moisture content, and the available fleet at the farm. The whole biomass can be harvested using a forage harvester or biomass harvester-baler [13], while seeds have to be harvested using a combine harvester [26]. The first attempts of Cynara seeds mechanical harvesting are dated back to the 90s, but machines could not cope with the high quantity of pappi released by the capitula during harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…According to this, costs of harvesting and logistic have to be evaluated, in order to make camelina cultivation fully sustainable and give support in the decision-making process to farmers and other stakeholders. Currently, mechanical harvesting of camelina is mainly carried out by using a combine harvester equipped with wheat header [33], only few experiences on cutting and swathing are reported [34]. However, seed loss can be very high, as a consequence of the tiny dimension of the seeds which are very small and light in weight [35,36] moreover, presence of weeds can further increase seed loss amount.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, castor mechanized harvesting needs to be improved due to the major losses, which can be up to 50% as evidenced by [48]. So far, only one machine manufacturer has started the first harvesting tests using a specific castor header, which would be able to reduce losses to 5% [48], and Zhao et al [49] reported the possibility to harvest the capsules using a vibrating system instead of a cutting bar [49]. In the present study, losses were not considered given the uncertainty of the data to be scientifically verified in specific tests.…”
Section: Resultsmentioning
confidence: 99%